Compressional wave velocity of hydrate-bearing bentheimer sediments with varying pore fillings - Sadeq, D.; Alef, K.; Iglauer, Stefan; Lebedev, Maxim; Barifcani, Ahmed (Elsevier Ltd, 2018)
© 2018 Hydrogen Energy Publications LLC A potential alternative energy resource to meet energy demands is the vast amount of gas stored in hydrate reserves. However, major challenges in terms of exploration and production surround profitable and effective exploitation of these reserves. The measurement of acoustic velocity is a useful method for exploration of gas hydrate reserves and can be an efficient method to characterize the hydrate-bearing sediments. In this study, the compressional wave velocity (P-wave velocity) of consolidated sediments (Bentheimer) with and without tetrahydrofuran hydrate-bearing pore fillings were measured using the pulse transmission method. The study has found that the P-wave velocity of consolidated sediments increase with increasing hydrate formation and confining pressure. Of the two samples tested, the increase in wave velocity of the dry and hydrate-bearing samples amounted to 27.6% and 31.9%, respectively. Interestingly, at the initial stage of hydrate formation, there was no change in P-wave velocity, which was followed by a steady increase as the hydrate crystals began to agglomerate and then it increased rapidly to a constant value, suggesting that the test solution had converted to a hydrate solid.